2011
DOI: 10.1242/jcs.076505
|View full text |Cite
|
Sign up to set email alerts
|

TβRI/Alk5-independent TβRII signaling to ERK1/2 in human skin cells according to distinct levels of TβRII expression

Abstract: TGFβ binding to the TGFβ receptor (TβR) activates R-Smad-dependent pathways, such as Smad2/3, and R-Smad-independent pathways, such as ERK1/2. The mechanism of the TGFβ–TβRII–TβRI–Smad2/3 pathway is established; however, it is not known how TGFβ activates ERK1/2. We show here that although TGFβ equally activated Smad2/3 in all cells, it selectively activated ERK1/2 in dermal cells and inhibited ERK1/2 in epidermal cells. These opposite effects correlated with the distinct expression levels of TβRII, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 21 publications
4
38
0
Order By: Relevance
“…A possible explanation for the different efficiency in TGF-b-induced Erk1/2 MAP kinase activation came from the study of TGF-b signaling in dermal versus epidermal cells. In dermal cells, where TbRII levels are high, TGFb efficiently activated Erk1/2, whereas in epidermal cells with low levels of TbRII, Erk1/2 activation was actually inhibited; artificial expression of TbRII in epidermal cells switched these cells to Erk1/2 activation in response to TGF-b stimulation (Bandyopadhyay et al 2011). In this study, activation of Erk1/2 MAP kinase was found to be TbRI-independent.…”
Section: Signaling Via Smad and Non-smad Pathwaysmentioning
confidence: 47%
“…A possible explanation for the different efficiency in TGF-b-induced Erk1/2 MAP kinase activation came from the study of TGF-b signaling in dermal versus epidermal cells. In dermal cells, where TbRII levels are high, TGFb efficiently activated Erk1/2, whereas in epidermal cells with low levels of TbRII, Erk1/2 activation was actually inhibited; artificial expression of TbRII in epidermal cells switched these cells to Erk1/2 activation in response to TGF-b stimulation (Bandyopadhyay et al 2011). In this study, activation of Erk1/2 MAP kinase was found to be TbRI-independent.…”
Section: Signaling Via Smad and Non-smad Pathwaysmentioning
confidence: 47%
“…Indeed, moesin was reported to interact with Rab11 and rescues defects associated with Rab11 deficiency, which may be a mechanism by which moesin could promote recycling of the TGF-β receptors (43). Our study focused on TβRII since TGF-β signaling can occur via TβRII independently of TβRI activation (44). Studies with cyclohexamide or BFA confirmed disruption in the stability of surface TβRII in moesin-deficient cells.…”
Section: Methodsmentioning
confidence: 80%
“…The mechanism of the TGF-b-TbRII-TbRI-Smad2/3 pathway has been well-established. TbRI knockout or TbRI inhibitortreated cells will block TGF-b-induced phosphorylation of Smad2, which means without TbRI only TbRII cannot induce the activation of TGF-b signaling [50,51]. Moreover, it was proofed that TGF receptor type I:type II ratio has an important role in the activation of TGF-b signaling and expression of TGF-b-induced genes [52].…”
Section: Discussionmentioning
confidence: 99%